Manajemen Hidden Curriculum pada Pembelajaran di Taman Pendidikan Al-Qur’an Integratif Roudhotul Ulum Kota Malang - Putri Restina Dewi (Ar-Rosikhun: Jurnal Manajemen Pendidikan Islam, 2021)
Management of hidden curriculum is the stage of hidden curriculum management in an educational institution. Each of these stages has its role in creating character during the learning process contained in HC in accordance with the objectives of educational institutions in this case at the Integrative TPQ of Roudhotul Ulum. This research aims to know and investigate hidden curriculum management, effectiveness and impact on learning at Integrative TPQ of Roudhotul Ulum. The research methods used are qualitative with a case study approach, and data collection techniques based on interview results, observations and documentation from the field. The results of this research are HC management processes consisting of planning, organizing, actuating and controlling. The effectiveness of HC on learning is evidenced by the ease of teachers in understanding the character of learners and the impact in the form of improving the quality of learning and improving the spirit of learning and the character of students.